The differential relationship of common health comorbidities with acculturative experiences in United States Latinxs. (September 2022) - Roth, Kimberly B.; Sanchez, Elizabeth; Musci, Rashelle J.
Highlights: A novel conceptualization of acculturation and related experiences is related to comorbidity. Different patterns emerge in the relationship between acculturative experiences and health. Toxic stress and social support may play differential roles in the risk for health comorbidities.